Inequalities in home learning and schools' provision of distance teaching during school closure of COVID-19 lockdown in the UK - Sait Bayrakdar; Ayse Guveli (University of Essex, Institute for Social and Economic Research (ISER), 2020)
Parents and schools were caught unprepared during the COVID-19 school closure. Since schools have a key role in creating equal opportunities, transferring schooling to families is likely to increase learning inequalities. Using the Understandings Society COVID-19 dataset, we find children who received free school meals, children from lower-educated and singleparent families and children with Pakistani or Bangladeshi backgrounds devote significantly less time to schoolwork at home. Schools' provisions of offline and online distance teaching and homework checking significantly increase the time children spend on home learning and mitigate most of the disadvantages.
Keywords: 330; Home learning; educational inequalities; schools; COVID-19; school closure